Thermal analysis of a micro device used for detection of colorectal cancer - Ahmed, Mirghani Ishak; Hrairi, Meftah (IIUM Press, 2011)
Finite element modelling is widely used in technological applications, The benefits of using simulation are clear; reduced time and cost when introducing new products to market, better knowledge of part dynamic and static properties, and the opportunity to replace life cycle device tests, among others. Finite element analysis (FEA) is extensively used in medical devices development cycle especially during the preliminary analysis of re-design and optimization and when passing the final design analysis and reliability evaluation. Typical analysis of implantable medical devices is challenging due to the highly nonlinear nature of the physical problem due to large geometric changes, contact and material behaviour. The current paper will investigate the design of a micro device intended for detection of colorectal cancer through a thermal analysis process and optimum sizing of air slits and side cuts between the different thermal zones of the device. By comparing the results of the numerous carried out simulations, an optimum design was found.